Cold-case Christianity : a homicide detective investigates the claims of the gospels - Wallace, J. Warner (Colorado Springs, CO : David C Cook, 2013)
"For the first thirty-five years of his life, J. Warner Wallace was a devout atheist. After all, how can you believe a claim made about an event in the distant past for which there is little forensic evidence? Then Wallace realized something. Christianity was a lot like the cold cases he solved as a homicide detective--cold cases that turned out to have enough evidence, eyewitnesses, and records to solve. When Wallace applied his skills as an expert detective to the assertions of the New Testament, he came to a startling realization: the case for Christianity was as convincing as any case he'd ever worked as a detective."--p. [4] of cover
Keywords: Jesus Christ -- historicity; Apologetics